Mapping charge to function relationships of the DNA mimic protein Ocr - Kanwar, Nisha (The University of Edinburgh, 2014)
This thesis investigates the functional consequences of neutralising the negative charges on the bacteriophage T7 antirestriction protein ocr. The ocr molecule is a small highly negatively charged, protein homodimer that mimics a short DNA duplex upon binding to the Type I Restriction Modification (RM) system. Thus, ocr facilitates phage infection by binding to and inactivating the host RM system. The aim of this study was to analyse the effect of reducing the negative charge on the ocr molecule by mutating the acidic residues of the protein. The ocr molecule (117 residues) is replete with Asp and Glu residues; each monomer of the homodimer contains 34 acidic residues. Our strategy was to begin with a synthetic gene in which all the acidic residues of ocr had been neutralised. This so called ‘positive ocr’ (or pocr) was used as a template to gradually reintroduce codons for acidic residues by adapting the ISOR strategy proposed by D.S.Tawfik. After each round of mutagenesis an average of 4-6 acidic residues were incorporated into pocr. In this fashion a series of mutant libraries in which acidic residues were progressively introduced into pocr was generated. A high-throughput in vivo selection assay was developed and validated by assessing the antirestriction behaviour of a number of mutants of the DNA mimic proteins wtOcr and Orf18 ArdA. Further to this, selective screening of the libraries allowed us to select clones that displayed antirestriction activity. These mutants were purified and in vitro characterisation confirmed these mutants as displaying the minimum number of acidic residues deemed critical for the activity of ocr. This in vitro process effectively simulated the evolution of the charge mimicry of ocr. Moreover, we were able to tune the high-throughput assay to different selection criteria in order to elucidate various levels of functionality and unexpected changes in phenotype. This approach enables us to map the “in vitro” evolution of ocr to identify acidic residues that are required for protein expression, solubility and function proceeding to a fully functional antirestriction protein.
Keywords: ocr; Type I Restriction Modification enzymes